2023
DOI: 10.1109/tvcg.2022.3196606
|View full text |Cite
|
Sign up to set email alerts
|

Distance Perception in Virtual Reality: A Meta-Analysis of the Effect of Head-Mounted Display Characteristics

Abstract: Distances are commonly underperceived in virtual reality (VR), and this finding has been documented repeatedly over more than two decades of research. Yet, there is evidence that perceived distance is more accurate in modern compared to older head-mounted displays (HMDs). This meta-analysis, based on 137 data points from 61 publications, describes egocentric distance perception across 20 HMDs and examines the relationship between perceived distance and technical HMD characteristics. Judged distance was positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 98 publications
0
24
1
Order By: Relevance
“…One potential explanation for a mechanistic shift to more ventral stream visuomotor control is the artificial presentations of distance cues used to perceive depth in an HMD-VR environment (Ganel and Goodale, 2003;Renner et al, 2013;Kelly, 2022;Kelly et al, 2022;refer to Harris et al, 2019 for a more detialed discussion). Briefly, depth perception occurs from incorporating both monocular cues (e.g., texture, shadows) and binocular cues (e.g., disparity, convergence).…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation for a mechanistic shift to more ventral stream visuomotor control is the artificial presentations of distance cues used to perceive depth in an HMD-VR environment (Ganel and Goodale, 2003;Renner et al, 2013;Kelly, 2022;Kelly et al, 2022;refer to Harris et al, 2019 for a more detialed discussion). Briefly, depth perception occurs from incorporating both monocular cues (e.g., texture, shadows) and binocular cues (e.g., disparity, convergence).…”
Section: Discussionmentioning
confidence: 99%
“…Renner et al [ 3 ] summarizes average egocentric distance estimation as 74% of the modelled distance, based on 78 articles published between 1993 and 2012. Kelly [ 5 ] found that the newest HMDs, on average, show distance estimation at about 82% of actual distance, which is improved, but still underestimated relative to the real world. Many factors have been examined as explanations for the underperception of scale including but not limited to: FOV and weight of HMDs [ 29 32 ], geometric distortions in displays [ 8 , 33 – 37 ], graphics quality or realism [ 28 , 38 40 ], pictorial or ground-surface cues [ 41 45 ], and response measures [ 38 , 46 , 47 ].…”
Section: Factors That Improve Distance Perception In Virtual Environm...mentioning
confidence: 99%
“…In the next two sections, we consider how changing HMD technology (which is associated with improved distance perception) could influence some of the information for absolute scale discussed in the earlier sections. First, the weight of the HMD has been directly [ 29 , 31 ] and indirectly [ 5 ] shown to affect distance perception. It is possible that wearing an HMD that increases weight on the head may affect how the angle of declination is computed or used.…”
Section: Factors That Improve Distance Perception In Virtual Environm...mentioning
confidence: 99%
See 2 more Smart Citations